Photosynthetic reaction center genes in green sulfur bacteria and in photosystem 1 are related. - Büttner, M (1992)
Oxygenic photosynthesis of chloroplasts and cyanobacteria involves two photosystems, which originate from different prokaryotic ancestors. The reaction center of photo-system 2 (PS2) is related to the well-characterized reaction center of purple bacteria, while the reaction center of photosystem 1 (PS1) is related to the green sulfur bacteria, as is convincingly documented here. An operon encoding the P840 reaction center of Chlorobium limicola f.sp. thiosulfatophilum has been cloned and sequenced. It contains two structural genes, coding for proteins of 730 and 232 amino acids. The first protein resembles the large subunits of the PS1 reaction center. Putative binding elements for the primary donor, P840 in Chlorobium and P700 in PS1, and for the acceptors A0, A1, and FeS center X are conserved. The second protein is related to the PS1 subunit carrying the FeS centers A and B. An adjacent third gene, not belonging to the reaction center, encodes a protein related to dolichyl-phosphate-D-mannose synthase from yeast. The different origins of PS1 and PS2 are discussed.